2017
DOI: 10.1073/pnas.1700231114
|View full text |Cite
|
Sign up to set email alerts
|

EBI3 regulates the NK cell response to mouse cytomegalovirus infection

Abstract: Natural killer (NK) cells are key mediators in the control of cytomegalovirus infection. Here, we show that Epstein-Barr virusinduced 3 (EBI3) is expressed by human NK cells after NKG2D or IL-12 plus IL-18 stimulation and by mouse NK cells during mouse cytomegalovirus (MCMV) infection. The induction of EBI3 protein expression in mouse NK cells is a late activation event. Thus, early activation events of NK cells, such as IFNγ production and CD69 expression, were not affected in EBI3-deficient (Ebi3 −/− ) C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…During MCMV infection, IL-21 induces mouse NK cells to produce IL-10, which affects dendritic cell activation and CD8 + T cell responses (38,(56)(57)(58). We also observed proliferative impairment of KLF12-deficient NK cells during MCMV infection in the mixed BM chimeric mice and in the adoptive transfer of mature NK cells.…”
Section: Discussionmentioning
confidence: 51%
“…During MCMV infection, IL-21 induces mouse NK cells to produce IL-10, which affects dendritic cell activation and CD8 + T cell responses (38,(56)(57)(58). We also observed proliferative impairment of KLF12-deficient NK cells during MCMV infection in the mixed BM chimeric mice and in the adoptive transfer of mature NK cells.…”
Section: Discussionmentioning
confidence: 51%
“…Using EBI3 −/− mice, several studies have reported that EBI3 regulates NK cell response and is involved in the establishment of mouse cytomegalovirus (MCMV) latency (Jensen et al . 2017 ), suppresses T helper type 1, type 17 and type 2 immune responses against Trypanosoma cruzi parasitemia (Bohme et al . 2016 ), and is associated with M. tb loads in mouse lungs (Zheng et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our previously published data show that Treg from aged mice have significantly increased levels of IL-35p19, suggesting that IL-35 may contribute to suppression of MCMV-specific CD8+ T cell responses [ 76 ]. However, a recent paper showed that IL-35 produced by NK cells during acute MCMV infection promotes, rather than inhibits IL-10 production [ 77 ]. Nonetheless, further studies are required to determine the mechanism by which Treg restrain MCMV-specific CD8+ T cell effector functions and thus promote latent infections.…”
Section: Discussionmentioning
confidence: 99%